Beyond the Syndrome: Extensive Congenital Abnormalities in an Infant With Trisomy 21 - Jeremy D Ward; Mahesh S Sharma; Matthew F Pizzuto; Vincent J Moylan; Frederic B Askin; David G Kaufman (SAGE Publishing, 2022)
Herein we discuss the clinical course and subsequent autopsy of a female infant with trisomy 21 with balanced Rastelli Type "C" complete atrioventricular septal defect (AVSD), tetralogy of Fallot and right aortic arch with mirror image branching pattern who underwent a palliative right modified Blalock-Taussig-Thomas shunt (mBTTS) for hypoxemia from progressive right ventricular outflow tract obstruction. The baby was found to have multiple concomitant pathologic findings not typically seen with this constellation of cardiac anatomy. Autopsy revealed significant abdominal adhesions with near-complete stenosis of the transverse colon. In addition, the infant was found to have significantly elongated villi within the small and large bowel and a relatively large collagenous polyp in the small bowel. The decedent also had an abnormal tracheal bronchus, characterized by an additional superior right-sided bronchus, which is an extremely rare abnormality. Her clinical course was complicated by severe pulmonary hypertensive arteriolar changes out of proportion to what would be typical for her age, trisomy 21 status, and degree of left to right intracardiac shunting. Furthermore, she had refractory anasarca and recurrent chylous pleural effusions without gross lymphatic abnormalities that may have been secondary to systemic capillary leak syndrome (SCLS) versus severe pulmonary hypertension. Due to the aforementioned findings, the family elected for comfort care and the baby expired shortly after extubation. Overall, the infant had multiple, rare coexisting congenital abnormalities that likely represents an extreme phenotype of trisomy 21 that has not been described in the literature to date.